Upaya Meningkatkan Kecerdasan Naturalis melalui Metode Bercocok Tanam pada Kelompok TK B di KB TK Asaloka Jakarta Barat Tahun Ajaran 2018/2019 - Dini Ameliawati (Neolectura, 2019)
The purpose in this research was to determine the process of implementing the planting method in an effort to improve naturalist intelligence for children. The method used in this study is a class action research method which consists of four steps, there are: planning, implementation, observation, and reflection. This research was conducted on 17 students at KB TK Asaloka on West Jakarta, from April to May 2019. The data collection techniques in this study were observation, field notes, interviews, and documentation. The results of the action in each cycle of class action research obtained an increase in children's naturalist intelligence from the start of the pre-cycle action with the acquisition of an average value are 1.3, or 32% if on percentage value. Cycle 1 get the acquisition of an average value 2.6, or 62% if on percentage value. Then, cycle 2 with the acquisition of an average value are 3.7, or equal to 92% on percentage value. The conclusion of this study is that planting methods are effective in increasing children's naturalist intelligence.